The Effect of GABAergic Cells Transplantation on Allodynia and Hyperalgesia in Neuropathic Animals: A Systematic Review With Meta-Analysis - Zhang, Zhen-Rong; Wu, Yao; Wang, Wen-Jing; Wang, Fang-Yong (Frontiers in Neurology, 2022)
The role of GABAergic cell transplantation in improving neuropathic pain is controversial. We comprehensively searched the relevant literature to identify animal studies of GABAergic cell transplantation that recorded pain behaviors as an outcome according to the Cochrane Handbook 5.0.2. Controlled studies assessing the administration of GABAergic neurons or GABAergic neuronal progenitor cells to rat or mouse neuropathic pain animal models were included. Basic design information and mechanical allodynia thresholds and heat hyperalgesia thresholds data were collected. The risk of bias for the animal experiments was assessed according to the SYRCLE's tool. This study included 10 full-text articles. GABAergic cells transplantation leads to a statistically significant improvement of allodynia (SMD = 5.26; 95% confidence interval: 3.02-7.51; P <0.001) and hyperalgesia (SMD: 4.10; 95% confidence interval: 1.84-6.35; P <0.001). Differentiated GABAergic cells and without antibiotics using may have a better effect for improving neuropathic pain. GABAergic cell transplantation is a promising treatment for improving neuropathic pain. This was the first systematic review and meta-analysis to evaluate the effects of GABAergic cell transplantation on neuropathic pain, which can guide future clinical trials and possible clinical treatments, and better attenuate neuropathic pain caused by abnormal circuit hyperexcitability.